2002
DOI: 10.1016/s0008-8846(02)00795-0
|View full text |Cite
|
Sign up to set email alerts
|

Porosity of recycled concrete with substitution of recycled concrete aggregate

Abstract: In this paper, we present the experimental analysis of samples of recycled concrete (RC) with replacement of natural aggregate (NA) by recycled aggregate originating from concrete (RCA). The results of the tests of mechanical properties of RC were used for comparison with tests of mercury intrusion porosimetry (MIP), in which the distribution of the theoretical pore radius, critical pore ratio, the surface area of the concrete, threshold ratio and average pore radius were studied at ages of 7, 28 and 90 days. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
204
1
23

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 548 publications
(246 citation statements)
references
References 3 publications
(1 reference statement)
18
204
1
23
Order By: Relevance
“…This leads to a change in stress distribution of mortar and aggregates over time during the creep process, both at early and latter ages. Similar findings have been reported by other authors (2,6,69,78,89,90), who noted largely higher (up to 84%) creep strains in concrete fully made with coarse recycled aggregates than in conventional concrete, while these increments lessened to 5-26% in concrete with low replacement ratios (20-30%) ( Figure 16). …”
Section: Creepsupporting
confidence: 90%
“…This leads to a change in stress distribution of mortar and aggregates over time during the creep process, both at early and latter ages. Similar findings have been reported by other authors (2,6,69,78,89,90), who noted largely higher (up to 84%) creep strains in concrete fully made with coarse recycled aggregates than in conventional concrete, while these increments lessened to 5-26% in concrete with low replacement ratios (20-30%) ( Figure 16). …”
Section: Creepsupporting
confidence: 90%
“…These values are quite similar to those obtained in different studies consulted in bibliography [18][19][20][21].…”
Section: Laboratory Testingsupporting
confidence: 90%
“…In agreement with the presented model, substituting the natural aggregate for the recycled aggregate results in a reduction of the deformation module for all of the aggregate types, which is consistent with many papers by other authors [14], [21], [22], [19]. It is also observed that substituting the coarse aggregate produces a greater effect in the module loss than substituting the fine aggregate, as a result of the magnitude of the coefficients found for them.…”
Section: Influence Of the Type Of Recycled Aggregate From Constructiosupporting
confidence: 91%